DC-operated Josephson junction arrays as a cryogenic on-chip microwave measurement platform - Senne Vervoort; Lukas Nulens; Davi A. D. Chaves; Heleen Dausy; Stijn Reniers; Mohamed Abouelela; Ivo P. C. Cools; Alejandro V. Silhanek; Margriet J. Van Bael; Bart Raes; Joris Van de Vondel (Communications Physics)
Abstract Providing radio frequency (RF) signals to cryogenic circuits requires bulky and expensive cabling interfacing specialized RF electronics at room temperature. Superconducting-normal metal-superconducting Josephson junction arrays (JJAs) can change this paradigm by placing the RF source and detector on-chip. In this work, we demonstrate that DC-biased JJAs can emit signals in the C-band frequency spectrum and beyond, with a minimal linewidth of 106.5 ± 0.1 MHz and maximum power of 11.9 fW. We fabricate JJAs comprised of amorphous MoGe or NbTiN superconducting islands and metallic Au weak links. Temperature, magnetic field, applied current, and device design are explored to control the RF sources, while we identify important features that affect the ideal source behavior. Combined with the ability of these JJAs to detect microwave radiation, these sources allow us to propose a fully DC-operated cryogenic on-chip measurement platform that is an alternative to the high-frequency circuitry currently required for quantum applications.